Բարդածանցավոր նորակազմ բաղադրությունները «Ազգ» շաբաթաթերթում (2015-2016 թթ.) - Մ. Ռ. Սողոմոնյան (ՀՀ ԳԱԱ հրատ.)
Среди неологизмов значительное место занимают сложно–производные с различными словообразовательными моделями. Они в основном связаны с научно–технической, медицинской, промышленной, спортивной и военной сферами. Compound words with various word-forming patterns are considerable among the language neologisms. They usually deal with the spheres of science and technology, medicine, industry, sports and the military sphere as well.
Keywords: Philology; Linguistics; Language and Literature